2022
DOI: 10.1002/pc.27083
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic analysis of nano‐barium ferrite reinforced casting polyurethane

Abstract: In this paper, barium ferrites (BFs) with an average particle size of 100 nanometers as filler are used to explore the improvement of the mechanical properties of casting polyurethane (CPU). The nano-BFs-filled CPU is prepared in situ by adding the suspension of nano-BFs in DMF to polyurethane precursor.The dynamic mechanical analysis is carried out to investigate the viscoelastic properties of nano-BFs-filled polyurethane. It is found that the strain energy density (SED) and the hysteresis energy density (HED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Typically, both the energy storage modulus G' and loss modulus G" gradually increase with the frequency. Meanwhile, the G' is larger than G" in the entire frequency range, indicating that the hydrogel network is completely elastic with a perfect covalent network [24]. In addition, the higher loss tangent (tan δ) is greater than 1 (Figure 2f), which demonstrates that the hydrogel has a high viscosity contribution.…”
Section: Thermal Property and Mechanical Property Of The Poly(aa-co-c...mentioning
confidence: 96%
“…Typically, both the energy storage modulus G' and loss modulus G" gradually increase with the frequency. Meanwhile, the G' is larger than G" in the entire frequency range, indicating that the hydrogel network is completely elastic with a perfect covalent network [24]. In addition, the higher loss tangent (tan δ) is greater than 1 (Figure 2f), which demonstrates that the hydrogel has a high viscosity contribution.…”
Section: Thermal Property and Mechanical Property Of The Poly(aa-co-c...mentioning
confidence: 96%
“…In our previous study, 118 the effect of barium ferrites (BFs) on the mechanical properties of PU was discussed. We found that the Tg of PU composites decreased first and then increased with the increase in BF content, which was due to the effect of improved microphase separation 43–47 .…”
Section: Effect Of Filler On Microphase Separation and Mechanical Pro...mentioning
confidence: 99%